Paradigma Baru Fungsi Pengarahan Di Dinas Lingkungan Hidup Sumatera Utara - Indriani Suci; Annio Indah Lestari Nasution (Universitas Labuhanbatu, 2022)
This study aims to determine the function of direction in the Department of environment of North Sumatra. This study uses qualitative description research method, this study uses primary data obtained by holding an interview with the head of ppkl at the North Sumatra Environmental Agency. In the research, the staff of the North Sumatera Environmental Agency understand the importance of directing functions in running their activities in the North sumatera Environmental Agency to function optimally and be able to carry out their respective roles and functions well and ensure that all work processes are carried out properly and correctly in Virtual Times. And the use of TAM in this study is a valid model to test the admissibility of well-conveyed information.